Grid Integrated Solar Energy Conversion System Using Super-Lift Converter - P, Elangovan; ., Kamatchi; ., Nandhini; Devi, Kamaatchi; ., Kokila (International Journal of Engineering and Technology, 2018)
Grid integrated photovoltaic (PV) system is capable of maximizing solar energy conversion by minimizing power losses. Conventionally, the grid integrated PV system uses boost or buck-boost DC-DC converters in the DC link for lifting up the PV output. Also, a separate complex circuit is used for active power compensation in the grid end. This paper proposes an advanced DC-DC converter by name Super-Lift Converter (SLC) in the DC link of grid integrated PV system. Unlike the conventional DC-DC converters, the proposed converter lifts up the DC link voltage thrice that of the input voltage. In addition, the proposed SLC is regulated using a PI controlled active front end (AFE) topology, which results in operation of unity power factor at grid end. The suggested system is simulated using MATLAB software. The presented results such as grid end voltage and current, input and output power of SLC and DC link voltage validates the effectiveness of the developed system.Â Â